1997
DOI: 10.1007/s003380050059
|View full text |Cite
|
Sign up to set email alerts
|

A unique coral reef formation discovered on the Great Astrolabe Reef, Fiji

Abstract: Abstract. A spectacular mound-like reef formation (126 m in circumference, 10 m high) dominated by highly arched and record-size colonies of the unattached mushroom coral Halomitra pileus, along with 17 other species of the family Fungiidae, occurs in 31 m of water on the sedimentary lagoon floor of the Great Astrolabe Reef, Fiji. Core samples show radiocarbon dates which indicate that the formation hypothetically began building &4500 y ago, with a calculated mean accretion rate of 2.2 mm · y\ . The majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…The evolutionary development of additional mouths over the upper surface in mushroom corals has resulted in the growth of larger coralla but also in a greater chance of survival during sedimentation-if one mouth is blocked by sediments, others remain intact (Hoeksema, 1991a;Gittenberger et al, 2011). In freeliving mushroom corals, budding or fragmentation in combination with regeneration and mobility facilitates continuous growth and may result in large and dense accumulations of specimens on sandy surfaces (Pichon, 1974;Littler et al, 1997;Hoeksema, 2004; Hoeksema and Gittenberger, 2010;Hoeksema and Waheed, 2011).…”
Section: Sedimentation: Feeding and Respirationmentioning
confidence: 97%
“…The evolutionary development of additional mouths over the upper surface in mushroom corals has resulted in the growth of larger coralla but also in a greater chance of survival during sedimentation-if one mouth is blocked by sediments, others remain intact (Hoeksema, 1991a;Gittenberger et al, 2011). In freeliving mushroom corals, budding or fragmentation in combination with regeneration and mobility facilitates continuous growth and may result in large and dense accumulations of specimens on sandy surfaces (Pichon, 1974;Littler et al, 1997;Hoeksema, 2004; Hoeksema and Gittenberger, 2010;Hoeksema and Waheed, 2011).…”
Section: Sedimentation: Feeding and Respirationmentioning
confidence: 97%
“…Thanks to their mobility and apparent re-sistance to toxins secreted by various sessile organisms, they usually survive when they happen to come in close contact with other competitors for space, either by growth or by bumping into them (Sheppard, 1979;Chadwick, 1988;Hoeksema, 1988;Chadwick-Furman and Loya, 1992;Yamashiro and Nishira, 1995;Abelson and Loya, 1999;Voogd et al, 2005). In free-living polystomatous corals, fragmentation in combination with regeneration and mobility facilitates continuous growth and may result in large surface areas of reef bottom to become covered by one or only a few species (Pichon, 1974;Littler et al, 1997;Hoeksema and Gittenberger, 2010), whereas monostomatous species clearly show determinate growth (Chadwick-Furman et al, 2000;Goffredo and Chadwick-Furman, 2003;Gilmour, 2004a;Knittweis et al, 2009). From an evolutionary perspective, polystomatism is probably not much constrained, since even in monostomatous mushroom coral species the production of secondary mouths can be induced artificially (Boschma, 1923;Jacoby et al, 2004), and as such it appears to be a plastic character in some fungiid species (Hoeksema, 1989).…”
Section: Ecomorphological Consequencesmentioning
confidence: 99%
“…2000; Miller & Mundy 2003). Furthermore, sessile organisms such as corals may undergo asexual reproduction by fragmentation and budding, which can cause dense stands of only a few species within a relatively large area because the propagules disperse and overgrow the substratum at the cost of other species (Hoeksema 1988; Hoeksema & Moka 1989; Nishihira & Poung‐In 1989; Hoeksema 1991a; Littler et al. 1997; Hoeksema 2004).…”
Section: Problemmentioning
confidence: 99%
“…corals) have shown that their dispersal distances may not be as great as has been previously suggested (Cowen et al 2000;Miller & Mundy 2003). Furthermore, sessile organisms such as corals may undergo asexual reproduction by fragmentation and budding, which can cause dense stands of only a few species within a relatively large area because the propagules disperse and overgrow the substratum at the cost of other species (Hoeksema 1988;Hoeksema & Moka 1989;Nishihira & Poung-In 1989;Hoeksema 1991a;Littler et al 1997;Hoeksema 2004). The limited dispersal distance compared to that suggested by the length of the larval period has also been demonstrated in studies of genetic connectivity between certain crustacean populations (Barber et al 2002;Palumbi 2003).…”
mentioning
confidence: 98%